Assessing the Impact of ENSO on Agriculture Over Africa Using Earth Observation Data - Sazib, Nazmus; Mladenova, lliana E.; Bolten, John D. (Frontiers in Sustainable Food Systems, 2020)
The El Niño–Southern Oscillation (ENSO) is one of the strongest drivers of climate variability, which directly influences agricultural production. The present study aims at assessing the impact of ENSO on agriculture in southern and eastern Africa by (1) exploring the association between ENSO, vegetation condition and soil moisture, and (2) analyzing the difference in soil moisture and vegetation condition for two extreme ENSO phases (El Niño and La Niña). Our results showed that vegetation conditions are significantly correlated with ENSO and exhibit a clear dipole pattern that reverses between El Niño and La Niña. Lagged correlation analysis confirmed the ability of soil moisture and ENSO to predict vegetation conditions. In general, the temporal and spatial evolution of soil moisture and vegetation responses showed the expected dipole pattern during the El Niño and following La Niña events. Results showed that ENSO impact on crop yield varied with geographic location, crop types, and ENSO phases. For example, yields in La Niña years have been higher in southern Africa but lower in eastern Africa. Maize yield decreases associated with El Niño events were usually larger than corresponding yield increases during La Niña events over southern Africa. Our findings highlight the impact of ENSO on agricultural production, which has significant potential to enhance the agriculture and food security-related early warning system.